Indonesian university students' likes and dislikes about emergency remote learning during the COVID-19 pandemic / Maila Dinia Husni Rahiem - Husni Rahiem, Maila Dinia (Universiti Teknologi MARA, 2021)
This study aimed to analyze what university students in Indonesia liked and disliked about the emergency remote learning process, which was implemented due to the COVID-19 pandemic. The case of Indonesia revealed what the majority of higher education institutions in developing countries faced during the COVID-10 period. This research used a qualitative phenomenological approach. There were 80 education students from the Faculty of Education state university in Jakarta, Indonesia who participated in the study. The inquiry consisted of a thorough study of participants' diaries of day-to-day learning and reflective essays and an online focus group of discussions. The results revealed what the students liked about learning from home during the COVID-19 crisis, which was grouped into three overarching themes of flexibility and efficiency, self-care and self-development, and learning new technology. What they disliked was grouped into three main themes: lack of structure, technological difficulties, and financial barriers. By knowing what students liked and disliked, we can try to reduce obstacles to their learning experience, and further improve the activities and features they liked. As a result, the quality of remote learning in this pandemic could be enhanced, and students' ability to study in any circumstances could be increased.